Relationship of Dialysis Adequacy with Depression and Anxiety in Hemodialysis Patients - Mohsen Nezami ghale noee; Hamideh Azimi lolaty; Jalil Hasani; Jamshid Yazdani-charati; Fatemeh Espahbodi; Hedayat Jafari (Mazandaran University of Medical Sciences, 2020)
Introduction and purpose: Chronic and debilitating diseases have many psychiatric consequences. Renal diseases followed by dialysis and kidney transplantation have a profound effect on the physical and mental health of individuals. This study aimed to determine the relationship of dialysis adequacy with depression and anxiety among hemodialysis patients in educational hospitals affiliated to Mazandaran University of Medical Sciences, Sari, Iran, in 2016. Methods: This cross-sectional study was performed on 185 patients with chronic renal failure under hemodialysis. The data were collected using a questionnaire consisting of three sections seeking information about demographic characteristics, disease variables, as well as anxiety and depression hospital scale.   Results: Out of 185 patients, the majority of the cases were male (n=101, 54.6%) with a mean age of 55±1 years and the females (n=84, 45.4%) were with a mean age of 59.8±0.85 years. About 49.5% of the subjects had urea reduction ratio ≥0.65 and KT/V≥1.2. Dialysis adequacy showed a significant relationship with feeling good, anxiety, and depression (P<0.001). Conclusion: Knowledge of factors related to dialysis adequacy and its promotion can increase the satisfaction of hemodialysis patients with the quality of dialysis and subsequently improve their quality of life.